Determinasi Keputusan Menabung Nasabah Non-Muslim pada Bank Syariah: Studi pada Bank Sumsel Babel Baturaja - Robiatul, Dea; Mustika Riantina, Eka (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2024)
This study aims to analyze the influence of product, service, brand image, and promotion on the saving decisions of non-Muslim customers at Bank Syariah Sumsel Babel, Baturaja Branch. The presence of non-Muslim customers in Islamic banking institutions represents an interesting phenomenon, as it reflects the acceptance of Islamic financial systems and values beyond the Muslim community. A quantitative approach was employed, with data collected through questionnaires distributed to 100 non-Muslim respondents. The data were analyzed using multiple linear regression with the assistance of SPSS software. The findings indicate that product, service, brand image, and promotion variables significantly affect saving decisions both partially and simultaneously. Among these factors, brand image was identified as the most dominant determinant influencing the saving decisions of non-Muslim customers. These results suggest that strengthening an inclusive Islamic brand image, supported by quality products, excellent services, and effective promotional strategies, enhances the attractiveness of Islamic banks to a diverse customer base. Therefore, this study contributes to the development of more inclusive and diversity-oriented marketing strategies in Islamic banking.